The Importance of Nutrients Concentration Monitoring In Coastal Area - Wisnu Arya Gemilang; Ulung Jantama Wisha; Ruzana Dhiauddin (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
Land utilization changes of the natural resources conservation area of Pangandaran coastal area, that have been utilized as a marine tourism area, which affect many kinds of environmental degradation threats. Updating the condition of Pangandaran waters is essential due to its condition impacted by anthropogenic activities. Water condition monitoring was done by measuring nutrients as an indicator to assess the water fertility and pollution. Fourty five observation points were selected and divided into three locations, representing the condition of river, estuary/mangrove area, and open sea. Nutrients were analyzed by employing Standard Methods for The Examination of Water and Wastewater 22nd Edition 2012 (SMEWW). Currents and tides were measured for 15 days, used as the basis input of hydrodynamic model. The results showed that the highest of average value of nitrate was found in the estuary/mangrove forest which reached 0.998 mg.L-1. While, the highest phosphate content was observed in the river which reached 0.928 mg.L-1. The highest ammonia concentration was observed in the sea which reached 0.027 mg.L-1. N:P ratios in the study area are categorized <16, which showed that Pangandaran waters are in the condition of N-limitation. These conditions trigger blooming of phytoplankton due to the high concentration of nitrate. The higher nutrient concentration indicates that anthropogenic activities take place. Tidal current has an important role transporting nutrient in the estuary, triggering nutrient deposition and blooming tendency. Restrictions on residential areas and the utilization of coastal areas are an appropriate step to reduce the pollution level in Pangandaran waters.